POLA PERJALANAN WISATA GENERASI MILENIAL DI SUMATERA BARAT - Suryani, Fadella; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to analyze the travel patterns of the millennial generation in West Sumatra. The millennial generation has unique characteristics and preferences in their travel behaviors, differing from previous generations. This research employs a descriptive method with data collection techniques including observation, documentation, and questionnaires. The collected data is analyzed using descriptive analysis, frequency analysis, and cross-tabulation analysis. The results show that millennials in West Sumatra tend to choose travel destinations that offer unique and authentic experiences. They also utilize information technology such as social media to plan and organize their trips. This research is expected to contribute to the development of the tourism industry in West Sumatra by understanding the needs and preferences of millennial tourists. Keywords: Travel Patterns, Millennial Tourism, West Sumatra, Travel Preferences, Tourism Industry.